2017
DOI: 10.1115/1.4038241
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the Effects of Reynolds Number and Advance Ratio on the Unfolding of Disorganization in Low-Speed Underwater Propulsors With Vibrating Blades

Abstract: Ships and submarines are acoustic hazards to marine life. The rational control of acoustic radiation would be possible at least at low Reynolds numbers if the underlying organization buried in seeming randomness is revealed. We build a novel low-speed propulsor where all blades undergo small-amplitude pitch oscillation while spinning at large pitch angles at transitional chord Reynolds numbers (3.75 × 103 ≤ Rec ≤ 3.75 × 104) and advance ratios (0.51 ≤ J ≤ 4.89). We measure and model time-averaged and temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…( a ) Plume array from kernels; Ri > 1.0 (middle), Ri = 1.0 (sides). ( b ) Unstable plumes in hot-cold side boundaries; numbers 1 and 2 on right show plume multistability; also shows advancing disorganization 33 in the middle plume cluster; however, only multistability is seen in the sides, triggered by a small increase in Ri from 1.0 and Re from 3.0. ( c ) Summary schema demonstrating the different stages of instability advance to chaos in varying physical domains, all co-existing.…”
Section: Resultsmentioning
confidence: 99%
“…( a ) Plume array from kernels; Ri > 1.0 (middle), Ri = 1.0 (sides). ( b ) Unstable plumes in hot-cold side boundaries; numbers 1 and 2 on right show plume multistability; also shows advancing disorganization 33 in the middle plume cluster; however, only multistability is seen in the sides, triggered by a small increase in Ri from 1.0 and Re from 3.0. ( c ) Summary schema demonstrating the different stages of instability advance to chaos in varying physical domains, all co-existing.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, Fig. 2 may be seen as a heuristic method of flow visualization or synthesis where there is an underlying limit cycle organization [8].…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the individual thrust oscillations do not "lock-in" because of the excess energy in the system per cycle of oscillation [7]. In a recent study in our laboratory on a conventional propulsor but with vibrating blades at transitional values of 3.75 Â 10 3 Re c 3.75 Â 10 4 , it has also been found that the emergence of patterns of disorganized limit cycles of thrust is episodic and not continuous [8]. This suggested that smaller animals have more initial condition-dependent mechanisms.…”
Section: Introductionmentioning
confidence: 95%